When do own-group biases in face recognition occur? encoding versus post-encoding - Young, Steven G.; Bernstein, Micahel J.; Hugenberg, Kurt (2010)
The Own-Group Bias in face recognition (the tendency to better recognize members of in-groups relative to out-groups) is a well-documented phenomenon in face perception. Although several theoretical models have been proposed to explain this robust phenomenon, no research directly addresses whether Own Group Biases occur during encoding, or occur post-encoding. Two experiments find that manipulations shown to improve other-group recognition (Experiments 1) and debilitate own-group recognition (Experiment 2) exert effects on face memory only when implemented prior to face encoding, but have no effect on recognition when administered post-encoding. Taken together, these data suggest that OGBs occur at encoding, rather than post-encoding. The theoretical and applied implications of these findings are discussed.